Chemical composition, antioxidant, antihemolytic and anti-inflammatory activities of Ononis mitissima L. (June 2020) - Besbas, Saliha; Mouffouk, Soumia; Haba, Hamada; Marcourt, Laurence; Wolfender, Jean-Luc; Benkhaled, Mohammed
Graphical abstract: Highlights: We study the chemical composition of the crude extracts (PE, EtOAc and n -BuOH) from Ononis mitissima L. A new trisnorlanostene-type triterpenoid and a new isoflavone are isolated and identified. It is the first report of a lanostane triterpenoid and an isoflavonoid with an HMG group in the Ononis species. The antioxidant, antihemolytic and anti-inflammatory activities were evaluated. Abstract: A new tris nor lanostene-type triterpenoid 25, 26, 27-tris nor -3α-hydroxy-lanost-7(8)-en-24-oic acid and a new isoflavone, formononetin-7- O -[6″- O -(( S )-3-hydroxy-3-methylglutaryl)]-β-d -glucopyranoside, in addition to twelve known compounds, were isolated from the ethyl acetate and n -butanolic extracts of Ononis mitissima L. Their structures were elucidated by spectroscopic analysis, including 1D and 2D NMR, mass spectrometry and comparison with literature data. The total phenolic and flavonoid contents were estimated. Furthermore, the antihemolytic and anti-inflammatory activities of the crude extracts (petroleum ether, ethyl acetate and n -butanol) were evaluated, as well as their antioxidant activity. The tested extracts displayed antioxidant activity on different methods including DPPH free radical scavenging activity, ferric reducing antioxidant power, ferric thiocyanate assay, hydrogen peroxide scavenging capacity and total antioxidant activity by phosphomolybdate assay. All extracts showed a moderate anti-inflammatory activity at the concentration of 500 μg/mL. The strongest antihemolytic activity was observed with the EtOAc extract.